Kid Cash Creative Money-Making Ideas - Lamancusa, Joe; Joe Lamancusa (Tab Books New York, 1993)
At least forty concrete, creative suggestions for ways to make money, with sample flyers for advertising oneself and information on setting fees, keeping records, and handling profits.
Includes Index
9 - 12 years
Keywords: New Business enterprises; Small business -- Management; Money-making projects for children -- Juvenile literature